Plate 3 from Amphitheatrum Sapientiae Aeternae, Solius, Verae [Amphitheatre of the Only True Eternal Wisdom] - Khunrath, Heinrich (Amphitheatrum Sapientiae Aeternae Solius Verae, 1609)
Plate 3 of Khunrath Heinrich's (1560-1605) Amphitheatrum Sapientiae, purportedly one of the most significant books of theosophical alchemy and the occult sciences. Though the title page reads 1602, the book was not published until 1609. Erasmus Wohlfahrt edited and published the manuscript following Heinrich's death in 1605. Wohlfahrt also added a preface and conclusion. The work contains masterful engravings, remarkable for their execution as well as alchemical symbolism. Nine double-paged copperplate engravings, a title page, and a frontispiece can be found in the digital collections. The engraving depicts a hilly landscape with a large cavernous tunnel at center. Figures of men stand in awe of the entrance and begin to climb the steps within the tunnel. This likely represents the gate to the "Amphitheater of Eternal Wisdom", "Porta Amphitheatri Sapientiae Ae'ernae."
Keywords: Alchemy; Christian art and symbolism; Theosophy; Engraving--Printing; Alchemy--Religious aspects; Alchemy in art; Occultism